(untitled) (Biological Sciences - PJSIR, 2024)
Nutritional profile of chapatti increased using other cereals and pulses. Hybrid wheat grown by crossing wheat varieties having high content of protein, Fe and Zn and used in combination with barley and chickpea. Therefore, current research was designed to check the effect of hybrid wheat on quality of chapatti in combination with chickpea and barley. So, different genotypes of hybrid wheat and one variety of barley and chickpea each were analyzed to assess physico-chemical properties, afterwards, hybrid wheat varieties milled into flour and mixed with barley and chickpea flour to prepare composite flour and to prepare chapatti at the end. Results showed TKW colour and protein contents ranged from 32.2-54.9 g, 15.3 to 20.4 and 10.55 to 19.50% respectively in hybrid wheats. NIR analysis revealed hardness of wheat genotypes varied from 66.34 to 86.9. Hybrid wheat varieties showed 2 to 6 min DDT and 24.7 to 38.3% wet glutin. In product, protein (18.79%), Fe (9.94 mg/100 g) and Zn (10.68 mg/100 g) of composite flour chapatti increased with the addition of chickpea and barley flour in hybrid wheat flour. Sensorial para- meters changed non-significantly, while in case of taste and chewing ability C1, C2 and C4, C5 showed better results than other compositions. Based on nutritional attributes and sensorial characteristics it is concluded that chickpea and barley were used at 25% and 15% in composite flour along with hybrid wheat varieties like B8, AR5 x PBICR#16 and AR7-4 x 29IBWSN-245.